2015
DOI: 10.1007/s00198-015-3124-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fragility fractures in Sakaiminato, Japan: incidence, secular trends, and prognosis

Abstract: The incidence rates of limb fractures in Sakaiminato were substantially lower than Caucasian populations in northern Europe but had increased relative to data obtained in Japan in the 1990s. Unlike upper and lower limb fractures, clinical vertebral fractures occurred at higher rates in our study population than in other Asian and North European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 42 publications
(58 reference statements)
1
53
1
Order By: Relevance
“…The results of this study, which encompassed the entire Japanese population aged 65 years and older, closely match the results of the previous studies performed in restricted regions of Japan, [7][8][9][10] by prefecture or city unit that assessed data trends pertaining to: (1) the highest number of fractures, regardless of age cohort for older people, occurring in patients with vertebral fractures, and (2) the second highest number of fractures occurring in patients with distal radius fractures for the earlier older age cohorts and patients with femoral neck fractures for the later older age cohorts, which were exponentially increased. These similarities strengthen the validity of our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study, which encompassed the entire Japanese population aged 65 years and older, closely match the results of the previous studies performed in restricted regions of Japan, [7][8][9][10] by prefecture or city unit that assessed data trends pertaining to: (1) the highest number of fractures, regardless of age cohort for older people, occurring in patients with vertebral fractures, and (2) the second highest number of fractures occurring in patients with distal radius fractures for the earlier older age cohorts and patients with femoral neck fractures for the later older age cohorts, which were exponentially increased. These similarities strengthen the validity of our study.…”
Section: Discussionsupporting
confidence: 89%
“…23) Second, for comorbidities, no attempt was made to improve the precision of the information by assessing modifier codes and any other examinations which could potentially introduce information bias. Third, we were not able to estimate the incidence rate of fractures or compare the incident rates in the previous regional studies performed inside [7][8][9][10] and outside 1,2,22) of Japan, because our data are derived from a polypharmacy study with a case-crossover design. In this study, fractures were recorded but there was no cohort of all older people in Japan who were relatively healthy, although that cohort is needed to calculate the incidence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,32 To compare rates of DRF in different countries, Table 1 49,50 ) and Africa (Nigeria 51 , Cameroon 52 ). Within each region, the publications are presented in chronological order according to the study period.…”
Section: Epidemiologymentioning
confidence: 99%
“…In previous studies conducted in Europe, North America, and Asia, the overall incidence rates of distal radius fracture have been shown to increase over time [6][7][8]. Other more recent studies have shown no change, or even a decrease, in the incidence [9][10][11].…”
Section: Introductionmentioning
confidence: 99%